Expert consensus statement to guide research into evidence-based classification of athletes for Para-Taekwondo – A Delphi study - Hee Seong Jeong; David M. O’Sullivan; Primoz R. Rus; Ashanti Ramírez Montes de Oca (Journal of Men's Health, 2021)
Background and Objective: The objective of this study was to investigate various issues surrounding participation in Para-Taekwondo Kyorugi (sparring), with the aim of focusing on future research initiatives to improve the classification system and safety for participation in Para-Taekwondo. Material and Methods: For this, a series of online questionnaires and in-person round-table discussions were conducted prior to the World Para-Taekwondo Championships (Antalya, Turkey, 2019), with a final online questionnaire thereafter. A select group of experts, such as athletes, coaches, administrators, classifiers, and athletes were invited to partake, with the main outcome measures being the expert opinions and ranking of importance for research into issues affecting Para Taekwondo athletes. Results: The results of the discuss provide suggestions and opinions for the following areas are provided for the aim of classification, minimum impairment criteria, fairness of classes, combination of classes, competition time, mixing of different impairments, safety of cerebral palsy athletes, weight classes, gender differences, intentional misrepresentation, personal protectors, time for re-classification, and research priorities. Conclusion: The most prevalent issue highlighted was the concern for athlete safety, especially for the K44 class, which has a mixture of neurological impairments, i.e. an athlete with mild cerebral palsy (CP) competing against an athlete with an amputation. Furthermore, on the issue of safety, developing protectors for athletes was another key issue raised. Therefore, in the future, we can strongly recommend research initiatives to examine the safety of athletes with various impairment types in the same class, and the development of protectors for Para Taekwondo athletes.